تجربة تركيا في تطبيق صيغ المشاركة في التمويل الإسلامي ودورها في تخفيف العبء على الموازنة العامة. (Journal of Economics and Management Research, 2025)
في ظل الضغوط المتزايدة على الموازنات العامة نتيجة الاعتماد على التمويل التقليدي، برز التمويل الإسلامي كبديل مستدام يركز على العدالة ومشاركة المخاطر. تُعد تجربة تركيا نموذجًا مهمًا في تطبيق صيغ المشاركة ضمن هذا النوع من التمويل، حيث ساهمت في تمويل مشاريع تنموية دون إثقال كاهل الميزانية بالديون. تهدف هذه الدراسة إلى تحليل هذه التجربة، من خلال استعراض الأطر النظرية للتمويل الإسلامي، وتطبيقاته العملية في تركيا، مع التركيز على التحديات والدروس المستفادة، بما يسمح بتقديم نموذج يمكن الاستفادة منه في دول أخرى تبحث عن حلول تمويلية أكثر استدامة. Amid increasing pressures on public budgets due to reliance on conventional financing, Islamic finance has emerged as a sustainable alternative focused on justice and risk sharing. Turkey's experience stands out as a notable example of applying partnership-based instruments, contributing to the financing of development projects without overburdening the budget with debt. This study aims to analyze Turkey’s experience by reviewing the theoretical foundations of Islamic finance and its practical applications, highlighting the challenges faced and lessons learned. The goal is to present a model that can be adapted by other countries seeking more sustainable and effective financing solutions.